2001
DOI: 10.1076/phbi.39.5.399.5889
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial Activity of the Crude Extracts and Fractionated Constituents of Myrtus communis

Abstract: The antibacterial activity of methanol crude extract of Myrtus communis L. (Myriaceae) was evaluated against 10 laboratory strains of microorganisms, including 6 Gram positive (Staphylococcus aureus, Micrococcus luteus, Streptococcus pneumoniae, Streptococcus pyogenes, Streptococcus agalactiae, Listeria monocytogenes) and 4 Gram negative bacteria (Escherichia coli, Proteus vulgaris, Pseudomonas aeruginosa and Campylobacter jejuni). The crude extract inhibited the growth of all tested bacteria except C. jejuni.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
42
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 88 publications
(49 citation statements)
references
References 6 publications
6
42
1
Order By: Relevance
“…Consistent with previous studies, the essential oil was active against both methicillin resistant and sensitive S. aureus at concentrations ranging from 4-8 μL/mL, 21,30,32 . In nosocomial infections, E. faecalis were isolated more often than E. faecium.…”
Section: Discussionsupporting
confidence: 73%
“…Consistent with previous studies, the essential oil was active against both methicillin resistant and sensitive S. aureus at concentrations ranging from 4-8 μL/mL, 21,30,32 . In nosocomial infections, E. faecalis were isolated more often than E. faecium.…”
Section: Discussionsupporting
confidence: 73%
“…However, considerable variability in the composition of oils from different locations has been reported (Olga, Stavros, & Ioanna, 2007). Although many plants from the Myrtaceae family are reported to have antibacterial or antifungal activities (Mansouri, Foroumadi, Ghaneie, & Gholamhosseinian, 2001;Shahidi, 2004), very little has been reported on the antioxidant activity of this plant (Hayder et al, 2004;Romani et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Ferulic acid were found in methanol (0,018 mg/g), ethanol (0,038 mg/g) and ethyl acetate (0,006 mg/g) extracts in low amounts while it was not determined in asetone extract. Other studies have shown mostly that essential oils of plant had strong antimicrobial activity [17][18][19][20]. However, It has known that classical extraction methods commonly used for the evaluation of antifungal activities of Myrtus communis.…”
Section: Resultsmentioning
confidence: 99%